Avaliação da influência do estresse e estímulos contextuais no desenvolvimento da dependência : abordagem comportamental e molecular - Carneiro de Oliveira, Paulo Eduardo (Universidade Federal de São Carlos, 2014)
This thesis is part of the requirements for obtaining Ph.D. title by Joint Graduate Program in Physiological Sciences, UFSCar/UNESP. The results presented refer to experiments developed in Laboratório de Neuropsicofarmacologia da Faculdade de Ciências Farmacêuticas de Araraquara and Behavioral Neurosciense Branch / National Institute on Drug Abuse - National Institutes of Health, Baltimore, USA. In chapter 1 we made a general introduction on the theories that formed the basis of the current concept of drug addiction. In this chapter, we elaborate a brief history of social organization and human relationship with drugs. We wrote specifically about both substances used in our studies, ethanol and cocaine, as well as their impact on public health and the pharmacological mechanisms of action. In chapter 2 the aim was to evaluate the influence of factors such as early age of onset of ethanol use and the effect of stress on the seeking behavior and consumption of this drug. For this, we used the animal model of ethanol self-administration and two types of social stress (social deprivation and social instability) in rats during adolescence. To verify whether behavioral changes were promoted by molecular neuroadaptations, we quantified gene expression involved in the development of ethanol dependence in amygdala, responsible area for stress-induce behaviors. In chapter 3 we investigated whether daun02 inactivation method is able to inhibit cocaine-induced locomotor sensitization in rats. This method is based on the theory that only a small group of sparsely distributed neurons (neuronal ensembles) are activated during behavior exhibition. For this purpose, we used transgenic rats carrying a c-fos-lacZ promoter which when activated induces the expression of ß-galactosidase enzyme only in activated neurons. The ß-galactosidase converts the prodrug daun02 into a toxic metabolite, driving to cell apoptosis. Thus, we evaluated whether the neuronal ensembles activated during the development of locomotor sensitization are the same as those recruited in the expression of this behavior. In chapter 4 we investigate whether mice express context-specific locomotor sensitization and whether the exhibiton of this behavior is related to synaptic changes in the nucleus accumbens. For this we use male and female transgenic C57BL/6 adult mice expressing Fos-GFP, a protein sensitive to green light, only in activated cells. Thus, using a confocal microscope, we assessed the presence of silent synapses only in activated neurons (neuronal ensembles) related to the expression of locomotor sensitization. Like us, researchers in the field of neurobiology of drug addiction have been studying the factors that can facilitate the initiation and maintenance of drug use and how it may trigger the addiction. Thus, this thesis aimed to investigate the influence of age, sex, stress, memory, associative learning, different types of drugs (cocaine and ethanol) and different types of animal models (self-administration and sensitization) in the development of drug addiction.
Keywords: Fisiologia; Adolescentes; Álcool; Estresse; Expressão gênica; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA DE ORGAOS E SISTEMAS::NEUROFISIOLOGIA